Gender gaps in sorghum productivity: evidence from male- and female-managed plots in Uganda - Miriti, Philip; Otieno, David Jakinda; Chimoita, Evans; Bikketi, Edward; Njuguna-Mungai, Esther; Ojiewo, Christopher Ochieng (Informa UK Limited, 2023)
Gender gaps in crop productivity can negatively affect rural socio-economic development of agrarian economies with serious implications for food and nutrition security. We assess productivity in male- and female-managed sorghum plots in Lira, Kumi, and Serere districts in Uganda. We find male-managed plots have higher productivity of 850.6 kgs/ha compared to female-managed plots (832.6 kgs/ha). An observed mean gender gap of 18% due to structural advantages of male plots (57%), structural disadvantages of female plots (33%), and endowment (10%) exists. Therefore, interventions aimed at promoting equitable access to institutional support services are paramount in reducing structural disadvantages against female farmers.